TROPONIN-I POSITIVITY IN PATIENTS REFERRED TO RAPID ACCESS CHEST PAIN CLINIC - Hayat, Umar; Motwani, Motwani J; Burrell, Burrell CJ (Journal of Ayub Medical College Abbottabad, 2010)
Background: Rapid Access Chest Pain Clinics (RACPCs) are set up to access patients with new onset chest pain (within the preceding three weeks), of possible cardiac origin. These patients are seen in the clinic within two weeks of referral and the attending physician takes a history, performs a routine clinical examination, and if clinically justified, a treadmill exercise test is performed according to Bruce Protocol. Within the group of patients referred to the RACPC with new onset but otherwise stable angina, there is a potential overlap with patients who in fact may have an evolving acute coronary syndrome, i.e., unstable angina. The aim of this study was to assess the prevalence of Troponin-I positivity as an indicator of acute coronary syndrome. Methods: This cross-sectional descriptive study included 60 consecutive patients referred to the RACPC with history of recent onset chest pain (within the last three weeks) of possible cardiac origin and positive ETT or confirmed abnormal ischemic ECG at baseline. Troponin-I was measured in these patients. Results: Out of the total 60 patients, 8.33% of the patients referred to RACPC with new onset angina had positive cTnI. Conclusion: Point of care test (POCT) for cTnI can help to identify the high risk patient referred to RACPC. Keywords: Troponin-I, cTnI, Troponin-T, Rapid Access Chest Pain Clinic, Angina, Unstable angina, Myocardial infarction, Non-ST elevation MI, Acute coronary syndrome